Optimizing ambulatory groin hernia repair in public healthcare frameworks: a prospective analysis of predictive factors for discharge failure - Jihen Krichen; Asma Sghaier; Rana Dhouib; Slah Souii; Maissa Tioumi; Sihem Sindi; Bilel Faidi; Khalil Ben Salah (Frontiers in Surgery, 2026)
Background Outpatient groin hernia repair is widely recommended globally due to clinical and socioeconomic efficiency, yet it remains underutilized in developing healthcare systems like Tunisia. This study aimed to evaluate the feasibility of a newly implemented day-surgery clinical pathway for groin hernias and identify specific predictors associated with outpatient discharge failure. Methods A prospective, observational cohort study was conducted at a Tunisian tertiary hospital between September 2023 and April 2024. A total of 85 consecutive patients scheduled for elective groin hernia repair under an optimized clinical pathway were enrolled. Inclusion criteria spanned ASA classes I–III, age ≥16 years, proximity to the hospital ≤50 km), and presence of a literate adult caregiver. Outpatient failure (unanticipated admission) was defined as the inability to achieve discharge within 24 h post-surgery. Statistical associations were determined using Chi-squared, Fisher's exact, and independent t-tests including direct comparative statistical evaluations of age, BMI, and baseline variables across stratified hernia orifice size groups. Results The cohort primarily comprised males ( n = 82, 96.5%) with a mean age of 56 years (range: 19–86). Successful ambulatory discharge was achieved in 80 patients (94.1%), yielding a failure rate of 5.9% ( n = 5). Unanticipated admissions were triggered by uncontrolled pain ( n = 1), acute anxiety ( n = 2), decompensation of comorbidities ( n = 1), and a Post-Anesthetic Discharge Scoring System (PADSS) score < 10 ( n = 1). Overall 30-day morbidity was low (2.4%), presenting as minor wound or scrotal hematomas managed conservatively; no surgical site infections, acute urinary retention, or mortality occurred. Univariate analysis revealed that hernia orifice size measured at its maximum diameter between 1.5 and 3 cm was significantly associated with ambulatory failure ( p = 0.047). General anesthesia showed a trend toward increased failure compared to regional anesthesia ( p = 0.08). Conclusion Day-surgery groin hernia repair is highly safe and feasible in resource-constrained environments, even for elderly or stable ASA III patients, provided rigorous social criteria are satisfied. A small hernia orifice size (1.5–3 cm) constitutes a major anatomical predictor of failure, likely due to distinct dissection dynamics and localized post-operative pain profiles.